The evaluation of senior world judo championships 2018 and 2019: the effects of sex and weight category on points, penalties, and match duration - Ceylan, B.; Balci, S. S. (Turkiye Klinikleri Journal of Sports Science, 2021)
Objective: This study aimed to determine the effects of sex and weight category on points, penalties, and match efficiency index after recent rule changes implemented between 2018-2020. Material and Methods: The data were obtained from a total of 1,664 matches. The effects of sex and weight categories on total match duration, match efficiency index scores for each athlete per match, the number of ippon, waza-ari, and penalties were tested with a two-way analysis of variance. Chi-square test was used to verify the relationship between sexes, match duration percentages, and percentages of the matches with and without the golden score. Significance was set at p<0.05. Results: Match durations and efficiency index scores were not affected by sex and weight category. However, the percentage of matches completed before the official duration in women was found higher than men. The duration of the matches decreased when the weight category increased for both sexes. When the weight category increased, the number of ippons increased, and the number of waza-ari decreased. The number of waza-ari was found higher in women compared to men. Interaction of sex and weight category on shido was found to be significant. The number of shido was higher in women and it increased with the increase in weight categories. Conclusion: It can be inferred from the study that the weight category factor affected ippon and waza-ari scores in the Senior World Championships. Although match efficiency score and total match duration were the same in men and women, women had a greater number of scores and penalties compared to men.